فعالية العلاج البيوطاقوي في التخفيض من الألكستيميا لدى المارهق المصاب بالربو - سعادنة خالد الأمين (جامعة البليدة 2؛ كلية العلوم الانسانية والاجتماعية, 2024)
هدفت الدارسة إلى التعرف على مدى فعالية العلاج البيوطاقوي في التخفيف من سيرورة الالكستيميا 18 و 14لدى المارهق المصاب بالربو، فشملت الدارسة أربعة حالات من المارهقين تتاروح أعمارهم بين سنة، وللإجابة عن تساؤلات الدارسة اعتمدنا على ثلاث أدوات لجمع البيانات وتمثلت في المقابلة نصف TAS الموجهة، مقياس الألكستيميا ( -) وكذا اختبار الرورشاخ، وذلك بالاعتماد على المنهج شبه 20 أشهر، وتوصلنا إلى النتائج التالية. 06التجريبي على مجموعة واحدة، بتطبيق اختبار قبلي وبعدي لمدة العلاج البيوطاقوي ساهم في التخفيف من سيرورة الألكستيميا حيث ل ّ فع التوظيف النفسي للحالات، ماسمح بتفعيل سيرورة التعقيل و بالتالي إلى الإرصان النفسي، ماسمح ببروز ابتسامات وأسلوب الطرفة وبالتالي صار ،لديهم، كما سهل العلاج البيوطاقوي للمارهق المصاب بالربو التعرف على انفعالاته يستطيع أن يعبر عنها لفظيا، كما ساهم العلاج البيوطاقوي في تنشيط الحياة الخيالية لدى الحالات من خلال عودة الأحلام وبروز بعض أحلام اليقظة، و كذا ظهور الهوامات ،بالإظافة إلى تقلص حديثهم عن الوصف الدقيق للأحداث وأعارض المرض. كما خفت حدة نوبات الربو لدى أغلب الحالات بعد العلاج. الكلمات المفتاحية العلاج البيوطاقوي، الألكستيميا، السيكوسوماتي، المارهق، الربو، الإرصان النفسي. The study aimed to identify the effectiveness of bioenergetic treatment in alleviating the process of alexithymia in adolescents with asthma. The study included four cases of adolescents between the ages of 14 and 18 years. To answer the questions of the study, we relied on three tools to collect data, which were the semi-directed interview and the alexithymia scale. (TAS-20) as well as the Rorschach test, relying on the quasi-experimental method on one group, applying a pre- and post-test for a period of 6 months, and we reached the following results. Bioenergetic treatment contributed to alleviating the process of alexithymia as it activated the psychological adjustment of the cases, allowing the process of mentalization to be activated and thus psychological sobriety, allowing for the emergence of smiles and the style of joking in them. Bioenergetic treatment also facilitated the adolescent with asthma to recognize his emotions, and thus he became able to express them verbally. Bioenergetic treatment also contributed to revitalizing the imaginative life of the cases through the return of dreams and the emergence of some daydreams, as well as the appearance of delusions, in addition to reducing their talk about accurate descriptions of events and symptoms of the disease. The severity of asthma attacks decreased in most cases after treatment. Key words Bioenergetic treatment, alexithymia, psychosomatics, adolescents, asthma, psychological sobriety
Keywords: العلاج البيوطاقوي،; الألكستيميا،; الربو،